Simultaneous topology and machine orientation optimization for multiaxis machining. (8th October 2021) - Gasick, Joshua; Qian, Xiaoping
Abstract: We present a density‐based topology optimization approach for multi‐axis machining where optimized designs can be machined by one or multiple axes. In our approach, density and machine axes can be simultaneously optimized. The fulcrum of our multi‐axis machinability based topology optimization approach is a formulation that characterizes machinability through inaccessible volume. This formulation is differentiable to both density and machining axes, and thus is amenable to gradient‐based optimization. We use an advection‐diffusion equation to facilitate the evaluation of inaccessible volume. Numerical examples on 2D and 3D linear elasticity problems are presented as a demonstration of the efficacy of this approach.